Modifying factors for the management of mineral resources and reserves of construction aggregates - Rafael Tadeu Pinto e Moura; Abdullahi Abba Dalhatu; Giorgio de Tomi (REM: International Engineering Journal)
Abstract This article proposes an industry-specific set of modifying factors for managing mineral resources and reserves for construction aggregates. To gain insights into the regional characteristics of the aggregate market and the requirement of situating mining operations close to urban centers, an application example was developed. It considers the two largest urban concentrations in Brazil to present findings on how the supply and demand of sand and crushed stone occurs in these regions and their relationship with the management of mineral resources and reserves. Furthermore, a conceptual simulation was conducted to showcase how limitations on mining areas can influence the conversion of mineral resources into aggregate mineral reserves. This simulation took into account different scenarios of environmental and social restrictions, which were identified as the primary bottlenecks in the quarries. The findings of the research highlighted the increasing significance of governmental and ESG-related modifying factors in aligning aggregates extraction activities co-existing with other land use in the vicinity. Finally, this article proposes a new indicator for classifying mineral reserves in this sector.